The Effect Of Financial Performance, Leverage, Good Corporate Governance And Company Size On The Sustainability Report (Study Of Companies Listed On The IDX, LQ 45 In Year 2015 – 2019) - NURDIN, Nurdin; RIYADI, Padlah (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:The research aims to determine the effect of financial performance, leverage, good corporate governance and company size on sustainability reports (study of companies listed on the LQ 45 2015 – 2019). Entity business management is currently not only based on economic aspects but also social aspects as the main basis for decision makers.Methodology:This study aims to determine and analyze the effect of profitability, leverage, institutional ownership, audit committee, independent commissioners, and company size on the sustainability reports of LQ 45 companies listed on the IDX in 2015-2019, so that 85 research samples were determined. Data was processed and analyzed using multiple linear regression.Findings:Related to sustainability in full and detail in the annual report or make a separate report regarding the company's social and environmental activities in the sustainability report or sustainability reporting. FOR Investors Investment is given to entities engaged in the natural resource management sector. Disclosure of sustainability reports is a consideration because entities that carry out and report corporate social responsibility will undoubtedly be more attractive to investors. After all, this gives legitimacy to the company's good value in the eyes of investors.Implication:Future research is expected to use different objects, such as companies in the manufacturing and mining sectors, which are directly correlated with environmental aspects and different indices, for example, SRI-KEHATI, LQ45, Kompas 100, and so on. The different research times and variables are also a suggestion for other researchers—the value of shares, aspects of capital, and other financial performance.